Výuka dovednosti myslet podle Edwarda de Bono - Málková, Gabriela (Lidé města, 2007)
Roughly from the 1970s, the topic commonly labeled “thinking skills” appears in the Anglo-Saxon psychology literature. It is very difficult to follow the unequivocal line of theoretical assumptions and predictors of birth of this topic. We may assume, that it has been strongly influenced by increased knowledge from the area of cognitive psychology and psychology of intelligence, cognitive, socio-cultural and socio-cognitive theory of learning and their application in teaching. This article introduces one of the first and probably the most important development program of thinking skills– the CoRT program. The author of this program is Edward De Bono. Since Do Bono’s work is very little known in the Czech environment, we devote part of this article to Edward de Bono himself and the theoretical system that basically represents foundation of all de Bono’s books. It is followed by description of CoRT methodology and an analysis of its theoretical context. Conclusion of the article discusses possible implementation of this program in the Czech environment.